Enhancing K-10 Students’ Conceptions through Computer Simulations-Aided PDEODE*E (CS-PDEODE*E) on Newton’s Laws - Fratiwi, N. J.; Samsudin, A.; Costu, B. (Jurnal Pendidikan IPA Indonesia, 2018)
The aim of this study was to enhance K-10 students’ conceptions through Computer Simulations-Aided PDEODE*E (CS-PDEODE*E) on Newton’s Laws. The PDEODE*E is a worksheet consisting of seven stages, which are Predict (P), Discuss (D), Explain (E), Observe (O), Discuss (D), Explore (E*) and Explain (E). The computer simulations could support learning via PDEODE*E worksheet by presenting physics’ phenomena. The Newton’s Laws focused on forces and Newton’s First Law. The research method used the 4D (Define, Design, Develop and Disseminate). The research sample included 30 K-10 students (15 boys and 15 girls, with the average age of 16 years-old). The students’ conceptions were identified through a Four-Tier Newtonian Test (FTNT) as pre- and post-test. In the developing phase, we acquired the product of computer simulations and PDEODE*E worksheet. In the disseminating phase, the value of effect size was 0.85 in the "large effect" of classification and tcount>ttable, thus, CS-PDEODE*E was more effective than CS-POE. The decisions succumbed that the students’ conceptions could be enhanced via PDEODE*E based computer simulations.